2018
DOI: 10.3390/rs10060956
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Variability of MODIS Phenological Indices in the Temperate Rainforest of Northern Patagonia

Abstract: Western Patagonia harbors unique and sparsely studied terrestrial ecosystems that are threatened by land use changes and exposure to basin-scale climatic variability. We assessed the performance of two satellite vegetation indices derived from MODIS-Terra, EVI (Enhanced Vegetation Index) and NDVI (Normalized Difference Vegetation Index), over the northern and southern sectors of the Chiloé Island System (CIS) to advance our understanding of vegetation dynamics in the region. Then we examined their time-varying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 53 publications
1
8
0
1
Order By: Relevance
“…This breakdown of the seasonal cycle and its relation to the antiphase between SAM (negative phase) and ENSO has been reported for the region before [16,24]. Briefly, after a prolonged near-neutral period during the early 2000's, the SAM experienced positive anomalies, firstly during the observed multidecadal antiphase with ENSO, and culminating with an in-phase period during the 2015-2016 warm ENSO event [39,64]. The latter climate pattern has been related to several phenological anomalies (e.g., anomalous timing of algal blooms), and local environmental disruption in the Inner Sea of Chiloé observed during the summer of 2016 [29,64].…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…This breakdown of the seasonal cycle and its relation to the antiphase between SAM (negative phase) and ENSO has been reported for the region before [16,24]. Briefly, after a prolonged near-neutral period during the early 2000's, the SAM experienced positive anomalies, firstly during the observed multidecadal antiphase with ENSO, and culminating with an in-phase period during the 2015-2016 warm ENSO event [39,64]. The latter climate pattern has been related to several phenological anomalies (e.g., anomalous timing of algal blooms), and local environmental disruption in the Inner Sea of Chiloé observed during the summer of 2016 [29,64].…”
Section: Discussionsupporting
confidence: 66%
“…The properties of vegetation indices derived from MODIS provide a substantially improved dataset for vegetation monitoring [34,41]. Recently, Lara et al [39] showed that EVI efficiently captures inter and intra-annual phenology pattern in Chiloé Island ecosystem. In this study, the authors suggested that the weakening in the spectral power of the vegetation activity in both northern and southern sections could be related to the change in the ocean-atmosphere conditions in the Pacific Ocean.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…where the Morlet wavelet ϕ(t) is the result of sine complex exp(−iw 0 t) and Gaussian wave package exp −t 2 f on /2 , t is the dimensionless time, w 0 is the dimensionless frequency, and π −1/4 is a standardized factor to ensure unit variance [37].…”
Section: Wavelet Analysis Of the Vcimentioning
confidence: 99%